SPIROMETRIC STUDY IN BRONCHIAL ASTHMA PATIENTS OF DIFFERENT AGE GROUPS - K.SIVANANDHAN,; NALINI SIVANANDHAN,; M.PALANISWAMY, (International Journal of Pharma and Bio Sciences, 2016)
Spirometric study was conducted for 83 bronchial asthma patients (43 males and 40 females) who attended the Asthma Research Centre, Pollachi to know the influence of height, age and gender of the patient, duration of suffering, Immunoglobulin E level and smoking upon spirometric values FEV1 and FEV1%. The patients were divided into six groups, depending upon their age (from 10 years to 60 years). The test was conducted using Helios – 702 electronic spirometer as per the guidelines of American Thoracic Society (ATS) statement on standardization of spirometry 1994 Update (1995). For an analysis of the spirometric results it was observed that the decline in spirometric values was more marked in shorter patients; the duration of illness had little effect up to 30 years of age; the duration of suffering and smoking caused a great decline after 40 years of age; gender and Immunoglobulin E level had insignificant influence upon spirometric values.